Ultra-Low Power Integrated Circuit Design Circuits, Systems, and Applications - Tan, Nianxiong Nick.; Li, Dongmei; Wang, Zhihua; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book describes the design of CMOS circuits for ultra-low power consumption including analog, radio frequency (RF), and digital signal processing circuits (DSP). The book addresses issues from circuit and system design to production design, and applies the ultra-low power circuits described to systems for digital hearing aids and capsule endoscope devices. Provides a valuable introduction to ultra-low power circuit design, aimed at practicing design engineers; Describes all key building blocks of ultra-low power circuits, from a systems perspective; Applies circuits and systems described to real product examples such as hearing aids and capsule endoscopes.
Interface to the Analog World -- Low Noise Low Power Amplifier -- Data Conversions -- Low Power Design Methodologies for Digital Signal Processors -- Ultra-Low Power Transceiver Design -- Low Power Energy Meter Chip -- A Single-Phrase Energy Metering SoC with IAS-DSP and Ultra Low Power Metering Mode -- SoC for Hearing Aids -- SoC for Capsule Endoscope.
Keywords: Engineering; Electronics; Systems engineering; Engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Signal, Image and Speech Processing